Eleições no Paraná: 1998 – 2010 - Omar Neto Fernandes Barros (Confins)
The theme of the elections in Brazil has been explored by several authors but with few linked to geography. At the moment, when once more several candidates postulate the leadership of the nation, States and Parliament, it seems to be opportune to make a reflection about this theme from a geographical point of view. Based on a cartographic documentation, the work has as an objective the analysis of results from the elections in the state of Paraná, in the period of 1998 - 2010, for the positions of Governor, including the production of the electoral-political spaces. The methodology of thematic cartography is a valuable instrument that allows the exploration of the statistic data mass by regions. The software used is Philcarto available at http://philcarto.free.fr. The principal results allow to reveal a regionalization of preferential votes on candidates, but these might change over time. With the maps analysis it became possible some predictions and confirmation for 2010.